Metformin Inhibits Advanced Glycation End Products (AGEs)-induced Growth and VEGF Expression in MCF-7 Breast Cancer Cells by Suppressing AGEs Receptor Expression via AMP-activated Protein Kinase - Ishibashi, Y.; Matsui, T.; Takeuchi, M.; Yamagishi, S. (Hormone and Metabolic Research, 2013)
Metformin use has been reported to decrease breast cancer incidence and mortality in diabetic patients. We have previously shown that advanced glycation end products (AGEs) and their receptor (RAGE) interaction stimulate growth and/or migration of pancreatic cancer and melanoma cells. However, effects of metformin on AGEs-RAGE axis in breast cancers remain unknown. We examined here whether and how metformin could block the AGEs-induced growth and vascular endothelial growth factor (VEGF) expression in MCF-7 breast cancer cells. Cell proliferation was measured with an electron coupling reagent WST-1 based colorimetric assay. Gene expression level was evaluated by real-time reverse-transcription polymerase chain reactions. AGEs significantly increased cell proliferation of MCF-7 cells, which was completely prevented by the treatment with 0.01 or 0.1 mM metformin or anti-RAGE antibodies. Furthermore, metformin at 0.01 mM completely suppressed the AGEs-induced upregulation of RAGE and VEGF mRNA levels in MCF-7 cells. An inhibitor of AMP-activated protein kinase, compound C significantly blocked the growth-inhibitory and RAGE and VEGF suppressing effects of metformin in AGEs-exposed MCF-7 cells. Our present study suggests that metformin could inhibit the AGEs-induced growth and VEGF expression in MCF-7 breast cancer cells by suppressing RAGE gene expression via AMP-activated protein kinase pathway. Metformin may protect against breast cancer expansion in diabetic patients by blocking the AGEs-RAGE axis.